The influence of the Indonesian ulema council's fatwa on cryptocurrency on cryptocurrency use by the millennial muslim generation - Inayatul Widad Nasution; Helvinasari Nasution; Iskandar Muda; Andri Soemitra; Yusrizal Yusrizal (Indonesia Auditing Research Journal, 2025)
This study investigates the influence of the Indonesian Ulema Council (MUI) Fatwa on cryptocurrency on the usage behavior of Muslim millennials in Indonesia. Employing a qualitative descriptive approach, data were collected through semi-structured interviews with eight respondents who actively use or are interested in cryptocurrencies. The data were analyzed using thematic analysis to identify key themes related to understanding, attitudes, and the practical impact of the fatwa. The findings reveal that most respondents are aware of the fatwa, which differentiates cryptocurrencies as haram when used as a currency and permissible as digital assets if they meet Shariah requirements, such as having underlying assets, clear benefits, and avoiding gharar, dharar, and qimar. Millennials’ responses were selective and adaptive: some abstained from using cryptocurrencies as money, while others continued investing with strategies to ensure compliance with Shariah principles. The fatwa exerts a moderate influence on usage decisions, moderated by respondents’ Shariah literacy, trust in religious authority, and pragmatic economic considerations. These findings suggest that while the MUI fatwa remains a relevant normative guideline, its effectiveness depends on the level of understanding and digital Shariah literacy among millennials. The study contributes to a better understanding of Muslim economic behavior, digital financial literacy, and the communication of religious guidance in the rapidly evolving context of fintech and digital assets.